Reduction of Blowholes in DC Modulated TIG Welding for Copper - et al., Toshifumi Yuji (International Journal of Advanced Science and Technology, 2019)
Welding the copper materials cause many welding defects such as blowholes and cracks, and the solution for these problems have been demanded. In this experiment, we succeeded to reduce the generation of blowholes during joining two types of copper materials, which are tough pitch copper (TPC) and oxygen-free copper (OFC) by utilizing the deep penetration characteristics obtained through pulse-modulated frequency in DC pulsed TIG welding. The results show that the number of blowholes generated in the butt welding between TPC materials and OFC materials were almost similar to the butt welding of OFC materials. In other words, the joining of the TPC and OFC capable to reduce the operation cost through reduction of materials cost, rather than using the expensive OFC materials at unnecessary place. In addition, the use of DC pulsed TIG welding rather than other complex welding system also capable to reduce the operation cost.